Current Trends in Treatment for Acid-Dependent Diseases: Clinical Efficacy and Safety of Rabeprazole - O. D. Lopina; B. K. Nurgalieva; T. L. Lapina (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Aim. A comparative review of the rabeprazole properties vs. other PPIs, its efficacy and safety in treatment for aciddependent diseases.Key points. Rabeprazole provides a rapid proton pump blockade in parietal cells due to its high dissociation constant (pKa). A lower rabeprazole metabolic dependence on cytochrome P-450 enzyme system renders its antisecretory effect predictable and reduces the risk of interactions with other drugs metabolised through this system. A faster antisecretory effect and higher acid-suppressive activity of rabeprazole determine its better clinical efficacy in treatment for such acid-dependent diseases as gastroesophageal reflux disease and peptic ulcer. This makes rabeprazole (Pariet) a preferred drug in course and maintenance therapies for acid-dependent diseases, as well as in H. pylori eradication.Conclusion. The rabeprazole properties of high acid suppression potential, persistent antisecretory effect from first day of therapy, non-enzymatic metabolism and pleiotropic action determine its high efficacy in treatment for a wide range of acid-dependent diseases at a minimal risk of drug interaction.